2013
DOI: 10.5606/ehc.2013.04
|View full text |Cite
|
Sign up to set email alerts
|

Carpal tunnel syndrome in manual tea harvesters

Abstract: Amaç: Bu çalışmada elle yapılan çay tarımına bağlı karpal tünel sendromunun (KTS) fizyopatolojik ve cerrahi boyutu, sinir ileti çalışmaları ve klinik skorlama sistemleri kullanarak değerlendirildi. Hastalar ve yöntemler: Şiddetli KTS nedeniyle cerrahi tedavi uygulanan 56 tarım işçisinin klinik ve nörofizyo-lojik skorları ile klinik ve mesleki değişkenleri; Boston anketi, İtalyan KTS çalışma grubunun modifiye kriterleri ve İtalyan KTS çalışma grubunun modifiye nörofizyolojik evreleme sistemi kullanılarak istati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
(36 reference statements)
0
8
0
1
Order By: Relevance
“…[1,2] Fibrosis of SSCT is a common histopathological finding in idiopathic CTS. [4,5] Although some research has been carried out on increased fibrosis of SSCT in idiopathic CTS, the exact mechanism which induce or facilitate fibrosis has not been established yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1,2] Fibrosis of SSCT is a common histopathological finding in idiopathic CTS. [4,5] Although some research has been carried out on increased fibrosis of SSCT in idiopathic CTS, the exact mechanism which induce or facilitate fibrosis has not been established yet.…”
Section: Discussionmentioning
confidence: 99%
“…[1] It has been previously suggested that a discordance between tissue volume and the size of the tunnel might cause this disease. [2] Previous studies have demonstrated neither morphometric nor biomechanical differences between transverse carpal ligaments in idiopathic CTS.…”
mentioning
confidence: 99%
“…KTS meslek ile ilişkili de olabilen yaygın bir sağlık problemidir (5)(6)(7)(8)(9)(10)(11). Titreşim içeren, el bileğini zorlayan hareketlerin sık yapılmasını; el ve el bileğinin uzun süre sabit pozisyonda tutulmasını gerektiren mesleklerde çalışan bireylerde KTS sıklığı artmaktadır (12).…”
Section: Discussionunclassified
“…In this study we found no significant effect of hobbies like knitting, sewing, doing house work and using computer on the severity of CTS for both the right and the left hand. In Turkey, Ciftdemir et al [15] investigated the prevalence of CTS related to manuel tea harvesting and reported that manuel tea harvesting might be a risk factor for work related CTS. And also we found no significant effect of smoking, diabetes mellitus, thyroid disease and rheumatoid arthritis on the severity of CTS.…”
Section: Discussionmentioning
confidence: 99%